Effect of Ammonium Nitrate on Nanoparticle Size Reduction. (9th April 2008) - Pingali, Kalyana C.; Deng, Shuguang; Rockstraw, David A.
Abstract : Ammonium nitrate was added to the spraying solution as a foaming agent to reduce the particle size of nanoparticles synthesized in the spray-pyrolysis process. Ammonium nitrate was effective in breaking the aerosol droplet size and generating nanoparticles that were of approximately one order-of-magnitude (from 200 to 20 nm) smaller diameter than those created in the absence of ammonium nitrate in the feed solution. This technique makes it possible to control the particle diameter of metallic nanoparticles below 20 nm.